Vapors of Volatile Plant-Derived Products Significantly Affect the Results of Antimicrobial, Antioxidative and Cytotoxicity Microplate-Based Assays - Houdkova, Marketa; Albarico, Genesis; Doskocil, Ivo; Tauchen, Jan; Urbanova, Klara; Tulin, Edgardo E; Kokoska, Ladislav (Molecules (Basel, Switzerland), 2020)
Volatile plant-derived products were observed to exhibit broad spectrum of biological effects. However, due to their volatility, results of conventional microplate-based bioassays can be significantly affected by the vapors. With aim to demonstrate this phenomenon, antimicrobial, antioxidant, and cytotoxic activities of three essential oils (Alpinia elegans, Cinnamomum iners, and Xanthostemon verdugonianus), one supercritical CO2 extract (Nigella sativa), and four plant-derived compounds (capsaicin, caryophyllene oxide, 8-hydroxyquinoline, and thymoquinone) were evaluated in series of experiments including both ethylene vinyl acetate (EVA) Capmat sealed and nonsealed microplates. The results clearly illustrate that vapor transition to adjoining wells causes false-positive results of bioassays performed in nonsealed microtiter plates. The microplate layout and a duration of the assay were demonstrated as the key aspects defining level of the results affection by the vapors of volatile agents. Additionally, we reported biological activities and chemical composition of essential oils from A. elegans seeds and X. verdugonianus leaves, which were, according to our best knowledge, analyzed for the first time. Considering our findings, certain modifications of conventional microplate-based assays are necessary (e.g., using EVA Capmat as vapor barrier) to obtain reliable results when biological properties of volatile agents are evaluated.
Keywords: biologické přípravky; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; antiinfekční látky; Antioxidants; Nigella; supercritical CO2 extract; Biphenyl Compounds; Candida albicans; Anti-Infective Agents; DPPH; Myrtaceae; rostlinné extrakty; Cinnamomum; Microbial Sensitivity Tests; broth microdilution; skořicovník; Staphylococcus aureus; Alpinia; bifenylové sloučeniny; MTT; antioxidancia; bioassay; Picrates; microtiter plate; Oils, Volatile; plant compounds; volatilization; essential oil; oleje prchavé; pikráty; těkavé organické sloučeniny; Plant Extracts; mikrobiální testy citlivosti; Biological Products; galgán; Volatile Organic Compounds